Organize your digital life : how to store your photographs, music, videos, and personal documents in a digital world - BALDRIDGE, Aimee (National Geographic Society, 2009)
This book helps you create a custom digital library and manage it like a professional. Inside, you will learn step by step how to decide what to keep and how, and much more. This book is ideal resource for teens who thrive on the technical, families with overflowing photo albums, and seniors who would love to collate a lifetime of letters and photo. With this first ever, easy to use guide, you will acquire the confidence and skills to master your digital universe.